Recognition of Pep-13/25 MAMPs of Phytophthora localizes to an RLK locus in Solanum microdontum - Lin, Xiao; Torres Ascurra, Yerisf Carla; Fillianti, Happyka; Dethier, Laura; de Rond, Laura; Domazakis, Emmanouil; Aguilera-Galvez, Carolina; Kiros, Afewerki Yohannes; Jacobsen, Evert; Visser, Richard G. F.; Nürnberger, Thorsten; Vleeshouwers, Vivianne G. A. A. (Frontiers in Plant Science, 2023)
Pattern-triggered immunity (PTI) in plants is mediated by cell surface-localized pattern recognition receptors (PRRs) upon perception of microbe-associated molecular pattern (MAMPs). MAMPs are conserved molecules across microbe species, or even kingdoms, and PRRs can confer broad-spectrum disease resistance. Pep-13/25 are well-characterized MAMPs in Phytophthora species, which are renowned devastating oomycete pathogens of potato and other plants, and for which genetic resistance is highly wanted. Pep-13/25 are derived from a 42 kDa transglutaminase GP42, but their cognate PRR has remained unknown. Here, we genetically mapped a novel surface immune receptor that recognizes Pep-25. By using effectoromics screening, we characterized the recognition spectrum of Pep-13/25 in diverse Solanaceae species. Response to Pep-13/25 was predominantly found in potato and related wild tuber-bearing Solanum species. Bulk-segregant RNA sequencing (BSR-Seq) and genetic mapping the response to Pep-25 led to a 0.081 cM region on the top of chromosome 3 in the wild potato species Solanum microdontum subsp. gigantophyllum. Some BAC clones in this region were isolated and sequenced, and we found the Pep-25 receptor locates in a complex receptor-like kinase (RLK) locus. This study is an important step toward the identification of the Pep-13/25 receptor, which can potentially lead to broad application in potato and various other hosts of Phytophthora species